2019
DOI: 10.5937/specedreh18-24824
|View full text |Cite
|
Sign up to set email alerts
|

Self-blame in parents of children with autism spectrum disorder and children with physical disabilities: The role of a child's problem behavior and personality traits

Abstract: Високо образовање је делатност од посебног значаја за Републику Србију и део је међународног, а посебно европског, образовног, научног, односно уметничког простора. Остварује се кроз академске и струковне студије на основу одобрених, односно акредитованих студијских програма за стицање високог образовања. Подаци о високом образовању су резултат редовних годишњих истраживања која се спроводе у свим високошколским установама и прикупљени су путем индивидуалних упитника. За уписане студенте то је "Статистички изв… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although denial can serve a protective function in helping one to cope in the short‐term, particularly for stressors perceived to be outside one's control (Woodman & Hauser‐Cram, 2013 ), it has generally been associated with worse mental health outcomes among family caregivers (Silva et al, 2015 ; Whittingham et al, 2013 ). Similarly, self‐blame has been examined in the context of some parents believing that they somehow contributed to their child having a disability and are being punished, especially in the absence of a medical explanation for their child's condition, or that they could be doing more for their child (Čolić & Milačić‐Vidojević, 2019 ), with one study showing parents' self‐blame to be associated with higher levels of caregiver burden, hopelessness, and depression (Moses, 2010 ). Interestingly, our results also showed that the use of specific adaptive coping strategies (i.e., emotional support, positive reframing, and acceptance) was associated with lower levels of stress, anxiety, and depression during the pandemic, although these associations were no longer significant when adjusting for other caregiver factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although denial can serve a protective function in helping one to cope in the short‐term, particularly for stressors perceived to be outside one's control (Woodman & Hauser‐Cram, 2013 ), it has generally been associated with worse mental health outcomes among family caregivers (Silva et al, 2015 ; Whittingham et al, 2013 ). Similarly, self‐blame has been examined in the context of some parents believing that they somehow contributed to their child having a disability and are being punished, especially in the absence of a medical explanation for their child's condition, or that they could be doing more for their child (Čolić & Milačić‐Vidojević, 2019 ), with one study showing parents' self‐blame to be associated with higher levels of caregiver burden, hopelessness, and depression (Moses, 2010 ). Interestingly, our results also showed that the use of specific adaptive coping strategies (i.e., emotional support, positive reframing, and acceptance) was associated with lower levels of stress, anxiety, and depression during the pandemic, although these associations were no longer significant when adjusting for other caregiver factors.…”
Section: Discussionmentioning
confidence: 99%